Evaluación técnica y económica para la implementación de tanques auxiliares en instalaciones de almacenamiento de refinados para la recuperación de hidrocarburo limpio (2024)
The objective of this degree work is the technical and economic evaluation for the implementation of auxiliary tanks in refined storage facilities for the recovery of clean hydrocarbon at the Salgar station. To do this, the amount of undefined refined product (PRND) or transmix that cannot be recovered in the API separators was quantified. An auxiliary tank, with a capacity of 300 gallons, was installed in the output lines of the JET storage tanks (TK - 151, TK - 138 and TK -150) with the objective of reducing the generation of product volumes outside of specifications when performing tank drainage processes. The amount of clean product recovered in barrels (bls) was quantified. Finally, an economic study of the project was carried out to evaluate its profitability over a period of five (5) years through the use of the financial indicators of the Net Present Value (NPV) and the Internal Rate of Return (IRR).